Tekstualitas vs Kontekstualitas:: Studi Kritis terhadap Penafsiran Ayat-ayat Sariqah dan Zina dalam The Message of The Qur’an - Najma, Dzatan; Musyarrofah; Mubarok, Nafi' (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
The emergence of dynamic problems of the people in aspects of life demands immediate responses and solutions. One of the dilemmatic problems is the sanctions for criminal acts of hudud. The holy text of the Qur'an which is relevant throughout the ages is expected to be a solution to these problems so that a rereading of the interpretation of the Qur'an is needed which contains elements of legal renewal that are in accordance with the context. The interpretation of The Message of The Qur'an is one of the contextual interpretations that is considered capable of overcoming today's problems. The formulation of the main problem in this study is how to analyze Muhammad Asad's interpretation in the interpretation of The Message of the Qur'an against the verses of hudud. This study is a library research with a qualitative approach using a descriptive-in-depth analysis method. The results of this study indicate that Muhammad Asad's interpretation of the verses of hudud, which in this study focuses on the verses of zian and sirqah, can be concluded in two ways. First, that Asad's interpretation of the verses of zina is classified as a textual interpretation because it still applies the punishment of caning in the current context. Meanwhile, Asad's interpretation of the sirqah verses includes contextual interpretation and can be applied today